2022
DOI: 10.1002/glia.24179
|View full text |Cite
|
Sign up to set email alerts
|

Microglia maintain the normal structure and function of the hippocampal astrocyte network

Abstract: Microglial control of activity‐dependent plasticity and synaptic remodeling in neuronal networks has been the subject of intense research in the past several years. Although microglia–neuron interactions have been extensively studied, less is known about how microglia influence astrocyte‐dependent control over neuronal structure and function. Here, we explored a role for microglia in regulating the structure and function of the astrocyte syncytium in mouse hippocampus. After depleting microglia using a CSF1R a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 98 publications
(162 reference statements)
3
27
0
Order By: Relevance
“…To identify the time hippocampal astrocytes fully connect into a syncytial network, we combined LY dye coupling and syncytial isopotentiality analyses to trace the functional maturation of the astrocyte syncytium in the mouse hippocampal CA1 region (Du et al, 2022; Kiyoshi & Zhou, 2019; Stephan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To identify the time hippocampal astrocytes fully connect into a syncytial network, we combined LY dye coupling and syncytial isopotentiality analyses to trace the functional maturation of the astrocyte syncytium in the mouse hippocampal CA1 region (Du et al, 2022; Kiyoshi & Zhou, 2019; Stephan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The syncytial isopotentiality measurement has already been used to study the mechanism among microglia‐astrocyte‐neurons crosstalk (Du et al, 2022), and changes in the functional state of an astrocyte syncytium in diseased conditions (Aten, Du, et al, 2022; Wang, Wang, et al, 2020). Now a variation of this method has been established and validated to examine the efficacy of the K + buffering within a syncytium under both physiological and pathological conditions in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, GFAP alterations are maintained upon microglia repopulation when treatment is discontinued (Basilico et al, 2021). Recently, it has been reported that CSF1R-i treatment weakens astrocyte gap junctional coupling (Du et al, 2022). Importantly, alterations in astrocytes have also been reported with genetic microglia depletion models (Bruttger et al, 2015;De Luca et al, 2020).…”
Section: Inhibition Of Colony Stimulating Factor 1 Receptor Signaling...mentioning
confidence: 99%